(3cJGH aj GdCOHs
(3ChdgG (B:s
(3jHJOF HGdaUd GdKGfi ef GdHGH GdQGHY ai Phi GdMadGf hCUMGH GdMSfGJ eQGLMI ai GdejRGf (B( (3aChd eG fHJOF HPcQ TF ef eMGSf GdfSGA ef cd af HOjY ZQjH eNJGQI ef cdGe GHf MHjH s
(3BNQgG (B:s
(3bGd GHQGgje adeG CUHMJ SGaQJ Edi GdHUQI adeG CJjJgG ETJQjJ gPG eG JjSQ LeYg hMSf hVYg ai gPG GdcJGH hfSCd Gddg GdhgGH Cf jQTOfG ddUhGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs